Construct-Inference-Process (CIP) Framework for UX Model Building and EvaluationOver Time - et.al, Azham Hussain (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This paper used a literature review strategy to investigate the approaches used in building user experience (UX) models and in evaluating UX over time. The paper reports that there is no uniform and consensus approach in the strategies used in developing user experience models and in evaluating UX over time. Researchers adopt divergent ways in building UX models and evaluating UX. This makes the development of a common approach difficult. It is also shown that there are three frequently employed approaches in the development of UX models and in the evaluation of UX over time. The three approaches are the construct, inference and process (CIP) approaches. The first two are associated with UX model development while the third is associated with UX evaluation over time utilizing the developed model. Researchers seldom use the three approaches combined together due to the rare use of longitudinal research in UX domain. Consequently, this paper strongly recommends and proposes the use of the combination of the three approaches to build UX models and to employ the developed model in evaluating UX over time.